2024
DOI: 10.1037/met0000477
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation modeling approach for modeling variability as a latent variable.

Abstract: Drawing upon recent developments in structural equation modeling, the current study presents an analytical framework for addressing research questions in which, rather than focusing on means, it is intraindividual (or intragroup) variability that is of direct research interest. Beyond merely serving as an alternative to existing multilevel modeling approaches, this framework allows for extensions to accommodate a variety of complex research scenarios by parameterizing variability as a latent variable that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…In our statistical models, there are two important aspects that might influence the results: nested data structures (i.e., individuals nested in teams) and the high empirical correlation between team psychological safety and climate strength (0.58). To investigate these two aspects at once, we followed up our first robustness analysis by conducting a structural equation model in which within-team variability (i.e., climate strength) was modeled as a random path coefficient at the between level (Feng & Hancock, 2022). 7 Specifically, we included team psychological safety and team performance at the individual level and utilized the log-transformation approach for modelling the individual level variance as a random variable at the team level (see Feng & Hancock, 2022, Model A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our statistical models, there are two important aspects that might influence the results: nested data structures (i.e., individuals nested in teams) and the high empirical correlation between team psychological safety and climate strength (0.58). To investigate these two aspects at once, we followed up our first robustness analysis by conducting a structural equation model in which within-team variability (i.e., climate strength) was modeled as a random path coefficient at the between level (Feng & Hancock, 2022). 7 Specifically, we included team psychological safety and team performance at the individual level and utilized the log-transformation approach for modelling the individual level variance as a random variable at the team level (see Feng & Hancock, 2022, Model A).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate these two aspects at once, we followed up our first robustness analysis by conducting a structural equation model in which within-team variability (i.e., climate strength) was modeled as a random path coefficient at the between level (Feng & Hancock, 2022). 7 Specifically, we included team psychological safety and team performance at the individual level and utilized the log-transformation approach for modelling the individual level variance as a random variable at the team level (see Feng & Hancock, 2022, Model A). To estimate the (cross-level) interaction effect between team psychological safety and climate strength, we used a partial approach in which the effect of team psychological safety on team performance at the individual level was modeled as a function of climate strength at the team level.…”
Section: Resultsmentioning
confidence: 99%
“…In many research and applied settings across the social, behavioral, and health sciences, it has been suggested that it is variability, rather than averages, that is of key interest (Feng & Hancock, 2022;Golino et al, 2022). To our knowledge, this is the first study that has examined inconsistency, dispersion, and variability of L2 development in relation to cognitive functioning and socioaffect in old adulthood; and it is also the first study that has investigated age differences in all three of the defined types of IAV simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, there has been increasing focus on the examination and manipulation of within-person variability in psychology, for example in the areas of clinical science (e.g., Naragon-Gainey, 2019;Russell et al, 2007), affective science (Houben et al, 2015), and human development (Nesselroade & Molenaar, 2010). Relatedly, new statistical approaches have emerged that enable estimation of within-person variability, including methods for modeling intensive longitudinal data (e.g., GIMME, Beltz & Gates, 2017; and dynamic structural equation models, Grimm & Ram, 2018) and isolating variance parameters as endogenous or exogenous variables in a structural equation model (Feng & Hancock, 2022;McNeish, 2021). Adding to the growing literature on individual variability, the present approach examines between-individuals, within-condition variability in slope estimates and its applications to comparing conditions in a clinical trial.…”
Section: Links To Related Approachesmentioning
confidence: 99%